Shared Prosperity in America's Communities - Wachter, Susan M.; Ding, Lei, 1974- (Book collections on Project MUSE., 2016)
Shared Prosperity in America's Communities examines the degree to which place matters in the geography of economic opportunity; offers strategies to address the challenges of place-based inequality; and shows how communities across the nation are implementing change and building a future of shared prosperity.